(3GdJMdjd hGdJNWjW GdeGdj (B:s (3GJLGgGJ eYGUQI (B/s - (3GdfYjej, YOfGf JGjgs; (3GdJejej, QTO aDGOs ((3YeGf(B: s (3OGQ GdjGRhQj(B, s, 2008)
(3jVe eONd Edi GdJMdjd GdeGdj, GdGJLGgGJ GdJbdjOjI dCOhGJ GdJMdjd GdeGdj GdJMdjd HGSJNOGe GdfSH GdeGdjI , GdGJLGgGJ GdMOjKI aj GdJMdjd GdeGdj , GdeaGgje GdGSGSjI aj GdJNWjW GdeGdj , JNWjW GdJOabGJ GdfbOjI h GdGMJjGLGJ GdeGdjI , GdJNWjW h GdQHMjI , JNWjW eNGWQ GdJOabGJ GdfbOjI (B.s
(3HjHdjhZQGajG(B: (3U(B.375- 382s
Keywords: (3GdGbJUGO GdJMdjdjs; (3GdJNWjWs; (3GdSjGSI GdeGdjIs